Bullying of Students in Academic Institutions: A Qualitative Study - Faieza Chowdhury (ÜNİVERSİTEPARK Limited, 2020)
Every student has the right to feel safe within their academic institution. However, many experience frequent bullying and undergo mental traumas, alienation and self-destructive behaviors. Bullying is largely an unreported and unaddressed issue in many academic institutions, which can result in long-lasting effects on students' lives. A study conducted by the United Nations Educational, Scientific and Cultural Organization (UNESCO), reported that 23% of school students in Bangladesh had been victims of bullying. This statistic clearly indicates that bullying is an alarming issue in Bangladesh which needs to be addressed urgently and properly. This qualitative study was conducted with 60 undergraduate students in order to explore their perceptions and experiences on bullying practices within the academic institutions of Bangladesh. Drawing on the findings of the study, a number of recommendations for the prevention and monitoring of bullying practices within the educational setting are suggested.